Liderazgo situado en el paradigma de la complejidad Docentes que construyen la nueva pedagogía, aquí y ahora - Marambio Carrasco, Cecilia Alejandra (Ariadna Ediciones, 2021)
The purpose of this work is to promote epistemic reflections related to the processes of pedagogical leadership in complex contexts, based on teaching and academic experiences, in the contexts of the current economic, health and social crises experienced by the world population and that weaken the students and teachers, during the years 2020 and 2021. The work is collective and the result of a call presented by the Ibero-American Research Center in Education, which called on teachers, academics and postgraduate students to share their experiences and reflections on how leadership in educational centers is expressed and educational contributions are expressed, of how to face the development of the Paradigm of Complexity (Morin, 2001), of how academics and teachers assumed the new pedagogy in the critical contexts caused by inequality, social crisis and of health, which confronts us with complex realities that fill us with uncertainties